Increased ambulatory arterial stiffness index in obese children. Issue 2 (February 2015) - Saner, Christoph; Simonetti, Giacomo D.; Wühl, Elke; Mullis, Primus E.; Janner, Marco
Abstract: Objective : Altered arterial stiffness is a recognized risk factor of poor cardiovascular health. Ambulatory arterial stiffness index (AASI, defined as one minus the regression slope of diastolic on systolic blood pressure values derived from a 24 h arterial blood pressure monitoring, ABPM) is an upcoming and readily available marker of arterial stiffness. Our hypothesis was that AASI is increased in obese children compared to age- and gender matched healthy subjects. Methods : AASI was calculated from ABPM in 101 obese children (BMI ≥ 1.88 SDS according to age- and sex-specific BMI charts), 45% girls, median BMI SDS 2.8 (interquartile range (IQR) 2.5–3.4), median age 11.5 years (9.1–13.4) and compared with an age and gender matched healthy control group of 71 subjects with median BMI SDS 0.0 (−0.8–0.5). Multivariate regression analysis was applied to identify significant independent factors explaining AASI variability in this population. Results : AASI was significantly higher in obese children compared to controls (0.388 (0.254–0.499) versus 0.190 (0.070–0.320), p  < 0.0001), but blood pressure values were similar. In a multivariate analysis including obese children only, AASI was independently predicted by 24-h systolic blood pressure SDS ( p  = 0.012); in a multivariate analysis including obese children and controls BMI SDS and pulse pressure independently influenced AASI ( p  < 0.001). Conclusions : This study shows that AASI, a surrogate marker of arterial stiffness, is increased in obese children. AASI seems to be influenced by BMI and pulse pressure independently of systolic and diastolic blood pressure values, suggesting that other factors are involved in increased arterial stiffness in obese children. Highlights: Ambulatory Arterial Stiffness Index is increased in obese children. BMI values independently influences Ambulatory Arterial Stiffness Index. Other factors than blood pressure increase arterial stiffness in obese children. Ambulatory arterial stiffness index might be a useful vascular marker in childhood.